Peace in Religious Teachings and its Impact on Economic and Political Stability - Abdul Rahim, Hafizah; Rahman, Asmak Ab (Jurnal Economia, 2024)
AbstractThis study aims to delve into the values of peace within Islam, Hinduism, Buddhism, and Christianity in Malaysia and its profound influence on the country's economic and political stability. This study employs a qualitative approach, utilising both primary and secondary sources. In-depth interviews were conducted with religious leaders representing Islam, Hinduism, Buddhism, and Christianity, while relevant documentation was used as a secondary source. The findings indicate the shared emphasis among religious leaders upon cultivating inner peace within their respective faiths. Each religion advocates that spiritual practices foster inner peace, contributing to a harmonious society, nation, and economic resilience. Conversely, neglecting these religious teachings can lead to violence, social issues, and an absence of peace within the country. Therefore, this study posits that peace holds immense significance, urging its integration among believers and indirectly impacting Malaysia's economic development and political stability. Keywords:Value of peace, religious teachings, economic and political stability.